2022
DOI: 10.1021/acs.jafc.2c04620
|View full text |Cite
|
Sign up to set email alerts
|

Light Quality Modulates Growth, Triggers Differential Accumulation of Phenolic Compounds, and Changes the Total Antioxidant Capacity in the Red Callus of Vitis davidii

Abstract: Light quality is one of the key elicitors that directly affect plant cell growth and biosynthesis of secondary metabolites. In this study, the red callus of spine grape was cultured under nine light qualities (namely, dark, white, red, yellow, blue, green, purple, warm-yellow, and warm-white light). The effects of different light qualities were studied on callus growth, accumulation of phenolic compounds, and total antioxidant capacity of the red callus of spine grape. The results showed that blue and purple l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…These results indicate that light plays an essential role in flavonoid biosynthesis. Several studies in different species have shown that light conditions induce flavonoid production [31,32] and antioxidant activity [33] higher than dark conditions. Dark conditions are assumed to be the most favorable conditions for D. esculenta callus growth.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate that light plays an essential role in flavonoid biosynthesis. Several studies in different species have shown that light conditions induce flavonoid production [31,32] and antioxidant activity [33] higher than dark conditions. Dark conditions are assumed to be the most favorable conditions for D. esculenta callus growth.…”
Section: Resultsmentioning
confidence: 99%
“…However, cyanidin-base anthocyanins were reported as the major colorant of plant fruits and seeds (Cevallos-Casals and Cisneros-Zevallos 2003; Khoo et al 2017; Seeram et al 2001). Especially, cyanidin 3-O-glucoside was reported as the major or one of the major anthocyanins metabolite in the different organs of woody plants, such as red-leaf of acer (Zhang et al 2021), red callus of Vitis davidii (Lai et al 2022), red anthers or leaves of poplar (Cho et al 2016; Kim et al 2021), and leaves of AmRosea 1 transgenic 84K poplar (Yan et al 2022). This study also illustrated that cyanidin-3-O-glucoside is the most abundant and absolutely dominant colorant in the sunlight-exposed poplar ARs, its content can up to 4115.17 ug/g in poplar red ARs.…”
Section: Discussionmentioning
confidence: 99%
“…Phenolic acids and flavonoids are crucial components of phenolic compounds. They not only contribute to callus formation but also help maintain ROS balance through their potent antioxidant and free radical scavenging abilities [38,39]. Additionally, previous research has shown that SNP treatment can inhibit the surface browning of fresh-cut apples by suppressing the synthesis of phenols, thereby reducing the total phenol content and promoting the accumulation of flavonoids [40].…”
Section: Discussionmentioning
confidence: 99%